Supply Chain Management in Fishing Industry: A Case Study - Sanjida Binte Islam; Dr. Mamun Habib (International Journal of Supply Chain Management, 2013)
The empirical research, based on primary and secondary data, represents the overall fish distribution system of Bangladesh with particular emphasis to the extent of value addition during the process of distribution. The data depicts the dynamics of relevant value-chains in fishing industry in Bangladesh that presents one of the developing countries in the world. This study encompasses the supply chain model of distribution of the fishing industry. The researchers demonstrate the distribution channel and the linkages between the relative benefits obtained as well as the outcome from the chain. This paper, which was based on the survey research technique, also highlights comparisons between domestic and regional value-chains with the view to understand better how developing countries can increase the value derived from their fishery resources. Consequently, the authors defined some recommendations and propose a new model which is free from the influence of the intermediate parties of any private sector and can reduce the usage of preservatives and increase the economical growth of all stakeholders' those are involved in the fishing industry.